2021
DOI: 10.1021/acssuschemeng.1c02126
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Photocatalytic Conversion of Carbon Dioxide by Water over Al-SrTiO3 Photocatalyst Modified with Silver–Metal Dual Cocatalysts

Abstract: In this study, an anisotropic facet-exposed Al-SrTiO 3 photocatalyst modified with various Ag−metal (Fe, Co, Ni, and Pt) dual cocatalysts was investigated to elucidate the functions of the Ag and metals in the photocatalytic conversion of CO 2 by H 2 O. The various dual cocatalysts were loaded on the surface of Al-SrTiO 3 using a simultaneous photodeposition method. In particular, the modification of the FeOOH and metallic Ag cocatalysts on the surface of the Al-SrTiO 3 photocatalyst markedly enhanced the CO f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…[20][21][22][23][24] The photocatalysis efficiency were roughly compared by CO yield. STONF 2 showed higher photocatalytic performance than reported CoAl LDH, MgAl LDH, ZnCr LDH, NiAl LDH, NiFe LDH, SrTiO 3 based photocatalysts, [25][26][27][28][29][30][31][32][33][34][35][36][37][38] as summarized in Table S1. †…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24] The photocatalysis efficiency were roughly compared by CO yield. STONF 2 showed higher photocatalytic performance than reported CoAl LDH, MgAl LDH, ZnCr LDH, NiAl LDH, NiFe LDH, SrTiO 3 based photocatalysts, [25][26][27][28][29][30][31][32][33][34][35][36][37][38] as summarized in Table S1. †…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that the carrier lifetimes of various photocatalysts will be elucidated by fluorescence lifetime measurements, TA spectroscopy, [43] and time‐resolved microwave spectroscopy, [44] and that photocatalysts and cocatalysts with high charge separation efficiency will be designed and developed based on the knowledge obtained [26ba,45] Previous studies have demonstrated that the catalytic activity can be enhanced when cocatalysts are loaded on suitable crystal facets for the reduction and oxidation reactions [28c,30n,o,46] . Therefore, it is expected that CRR photocatalysts with improved activity and selectivity will be developed in the future by establishing methods to selectively load cocatalysts that have size, alloy structures, crystal facets, and shell structures suitable for achieving high activity and selectivity on the crystal facets of the photocatalysts where CRR occurs. It is expected that the geometric structure of highly active and selective cocatalysts will be revealed at the atomic level by aberration‐corrected TEM and STEM [47] measurements, thereby providing a clearer understanding of the effect of surface structure on catalytic activity. Atomically precise metal nanoclusters (NCs), [48] whose geometric/electronic structures have been revealed by single‐crystal X‐ray structural analysis and DFT calculations have been reported to be highly active cocatalysts for photocatalytic water‐splitting reaction and other catalytic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the specific surface structure of the photocatalyst cannot be ignored in the process of CO 2 reduction [34,35]. Due to the eight-electron reaction of CH 4 generation from CO 2 , loading co-catalysts with fast electron transfer, including Au, Pt, Ag and Ti, could be conductive to control the reduction of products [35][36][37][38]. Non-noble-metal Cu co-catalyst has become a newly emerging research spot for CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%